Banking - Sultanova, Zamzagul Khamitovna (Zhangir Khan West Kazakhstan Agrarian-Technical University, 2020)
The textbook is completed according to the syllabus of the subject. The textbook consists of the theoretical and practical materials for barchelor students.
Banking : textbook for students of the economic specialties / Z. Kh. Sultanova. - Uralsk : Zhangir Khan West Kazakhstan Agrarian-Technical University, 2020. - 128 p. - ISBN 978-601-7636-85-2 : Б. ц.
Keywords: рк; казахстан; зкату; поступление 2020; умо; экономические специальности; учебники; полиязычие; банки; банковское дело; финансы; textbook; finance; banking; banks; multilinguism